Local knowledge of agricultural biodiversity and food uses of edible plant species in two agroecological zones of southern Benin - Koukou, Elie; Amoussa Hounkpatin, Waliou; Sognigbé, N'Danikou; Sounouke, Comlan Vincent De Paul; Ntandou-Bouzitou, Gervais D.; Termote, Céline (Ilia State University (Georgia), 2022)
Locally available food plants are not only a good source of essential micronutrients but also provided culturally acceptable foods. Their evaluation could be a sustainable strategy that can effectively meet the nutrient requirements for vulnerable groupsin rural areas. They are therefore of great importance in ensuring food security in low-and middle-income countries. Several communities in Benin depend mainly on indigenous food sources especially plant species. An ethnobotanical survey was conducted in southern Benin to document the edible plant species (EPS) used by people living in two agroecological zones (AEZ 6 and AEZ 8). Field investigations were carried out in eight villages of the two agroecological zones, with four villages per agroecological zone. Data were collected through focus group discussions (FGDs) and analyzed using descriptive statistics. A total of 146 edible plant species belonging to 46 families were recorded and herbarium specimens were collected and deposited at the national herbarium of Benin. Species diversity was lower in AEZ 6 compared with AEZ 8. Herbs and shrubs were the dominant plant habits, with leaves and fruits (arils, flesh, pulp) as the most reported plant parts that were consumed mainly as leafy vegetables or fruits. The study area harbors an important plant diversity with high nutritional potential. Nutrient-dense leafy vegetables and fruit species were dominant. This represents an opportunity that could be used to improve the diet quality and food security in the study area. However, the locally available food plant species remain undervalued.